2006
DOI: 10.1016/j.freeradbiomed.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and oxidant signaling in obstructive sleep apnea and associated cardiovascular diseases

Abstract: Obstructive sleep apnea (OSA) has emerged as a major public health problem and increasing evidence indicates that untreated OSA can lead to the development of various cardiovascular disorders. One important mechanism by which OSA may promote cardiovascular diseases is intermittent hypoxia, in which patients are subjected to repeated episodes of brief oxygen desaturation in the blood, followed by reoxygenation. Such cycles of hypoxia/reoxygenation may result in the generation of reactive oxygen species. Some st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
124
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 108 publications
2
124
0
8
Order By: Relevance
“…[97][98][99] Some studies have reported increased levels of thiobarbituric acid reactive substances, isoprostanes, and oxidized low-density lipoprotein in OSA, 100 although these changes have not been confirmed in other studies. 101 Circulating free nitrotyrosine, a marker of nitrosative oxidative stress, is not elevated in OSA patients.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…[97][98][99] Some studies have reported increased levels of thiobarbituric acid reactive substances, isoprostanes, and oxidized low-density lipoprotein in OSA, 100 although these changes have not been confirmed in other studies. 101 Circulating free nitrotyrosine, a marker of nitrosative oxidative stress, is not elevated in OSA patients.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…As alterações repetidas na saturação sangüínea, presentes nos episó-dios de apnéia/hipopnéia e hipóxia-reoxigenação da AOS são similares ao quadro da injúria isquemia-reperfusão tecidual, promovendo danos aos vasos sangüíneos quando o fluxo é restaurado, em razão do aumento da produção de radicais livres (19,20). Estas espécies reativas de oxigênio reagem com ácidos nucléicos, lipídeos e proteínas e ainda reduzem a produção de nitritos e nitratos séricos, causando lesão endotelial, fator de risco fortemente associado às doenças cardiovasculares (21,22).…”
Section: Introductionunclassified
“…Though the cause for such abnormalities in OSA is not clear, oxidative stress has been proposed to be one of the important factors in the pathogenesis of these metabolic abnormalities. The chronic nocturnal intermittent hypoxia occurring in OSA mimics ischemia-reperfusion injury that has been associated with increased production of vascular ROS which promotes oxidative stress [5]. We also found a significant reduction of lipid peroxidation after one night of CPAP treatment [Table/ Fig-3].…”
Section: Discussionmentioning
confidence: 66%
“…In India the prevalence of OSA is estimated to be 13.7% [2] and the prevalence of metabolic syndrome in OSA patients ranges from 4.5% in population-based study [3] to 79% among patients with OSA in hospital-based study [4]. There is cumulative evidence suggesting the presence of increased oxidative stress in OSA patients [5]. In our previously published study we have demonstrated an increased lipid peroxidation and decreased total reduced glutathione levels indicating an imbalance between reactive oxygen species (ROS) and antioxidant capacity [6].…”
Section: Introductionmentioning
confidence: 99%